Kryzys filozofii polityki - Markowska, Barbara (Civitas. Studia z filozofii polityki, 2011)
The purport of the article is a reflection on the operating conditions of the philosophy of politics, beginning with its crisis, as described by Leo Strauss in the early 20th century and continuing up to the latest proposals, which emerged at the turn of the 20th and 21st centuries. First, the author poses a question regarding the essence of this crisis; was it related to the scientific paradigm of the philosophy of politics applied hitherto or, rather, to the very subject matter of this scholarly pursuit, which is to say, to politics itself. A scientific discipline must be able to delineate its subject matter and if the latter undergoes an unexpected modification, the former suffers a crisis. Was this what happened to politics itself? What was the decisive factor which caused it to escape a theoretical consideration that ceased to be a systematic reflection, in short, ceased to be science, only to become philosophy again, whereby the author understands ‘philosophy’ as a level of reflection such as to allow itself to posit subliminal questions purely in order to set up the determinants for further thinking as to what science is, what politics is and what makes politics different from non-politics.